“Optimización del proceso de molienda para la recuperación de mineral Oro (Au) en la Planta de Beneficio MAFRE código 390379, ubicado en el sector El Salado, de la Parroquia Portovelo, del Cantón Portovelo de la Jurisdicción de la provincia de El Oro”. - Atarihuana Sandoval, Celso Xavier (2025)
The present investigation “Optimization of the milling process for the recovery of gold ore (Au) in the beneficiation plant MAFRE code 390379 located in the El Salado sector, in the Portovelo parish, in the Portovelo canton, of the Jurisdiction of the province of El Oro”, was carried out to improve the conditions of the current milling process since it does not manage to recover the expected optimum amount of gold, associated to the milling process. The methodological approach used was analytical and synthetic, gathering mining and metallurgical information in the area, with geological sampling and physical, chemical and mineralogical analysis to determine the optimum degree and time of milling. The gold extraction process started with ore crushing in Chilean mills, followed by gravimetry, cyanidation and elution. A grade of 16.50 g/ton in the ore and 1.13 g/ton in the tailings was found, indicating significant losses and the need to optimize recovery. Regarding the physical-mechanical and mineralogical properties, the plant is located in the Zaruma-Portovelo Mining District, on quaternary alluvial deposits, with extrusive volcanic rocks, mainly andesitic breccias, which contain SiO2 and CaCO3 and present a simple compressive strength that supports considerable loads. From this context, grinding parameters were adjusted, achieving a volume of 0.041 m3, a filling degree of 26%, a balls diameter of 1.29 inches, and an optimum particle size of 75 microns; to verify the efficiency of the circuit after grinding, the sample was sent to the Albexxus laboratory, where a gold content of 13.12 g/ton was obtained, with 12.80 g/ton recoverable by cyanidation, using 4.126 kg of lime and 12.048 kg of cyanide per ton. Finally, an optimized circuit was proposed that includes trituration, ball mill and a hydrocyclone to remove particles larger than 75 microns, guaranteeing an efficient milling process for the recovery of gold ore in the “MAFRE” beneficiation plant.